2019
DOI: 10.1002/ajp.23003
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and metabolome of saddleback tamarins (Leontocebus weddelli): Insights into the foraging ecology of a small‐bodied primate

Abstract: Body mass is a strong predictor of diet and nutritional requirements across a wide range of mammalian taxa. In the case of small-bodied primates, because of their limited gut volume, rapid food passage rate, and high metabolic rate, they are hypothesized to maintain high digestive efficiency by exploiting foods rich in protein, fats, and readily available energy. However, our understanding of the dietary requirements of wild primates is limited because little is known concerning the contributions of their gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Dominant genera included Bifidobacterium , Bacteroides , Collinsella , Prevotella , Alloprevotella , Parabacteroides , Phascolarctobacterium , Megamonas , Megasphaera , and Escherichia ( Table S1B ). In the majority of the animals, Bifidobacterium was the most abundant genus (range, 6 to 64%; median, 26%), and this characteristic has been reported in several other captive marmoset populations ( 31 , 40 43 ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Dominant genera included Bifidobacterium , Bacteroides , Collinsella , Prevotella , Alloprevotella , Parabacteroides , Phascolarctobacterium , Megamonas , Megasphaera , and Escherichia ( Table S1B ). In the majority of the animals, Bifidobacterium was the most abundant genus (range, 6 to 64%; median, 26%), and this characteristic has been reported in several other captive marmoset populations ( 31 , 40 43 ).…”
Section: Resultssupporting
confidence: 56%
“…The marmoset is an emerging nonhuman primate model with several characteristics that make it a tractable model for studying the microbiome, and marmoset microbiomes are actively being studied in several different marmoset colonies and wild callitrichid populations ( 40 43 , 77 ). One of the most distinctive features shared by animals across multiple facilities, including the CRC, is the dominance of their microbiomes by species of Bifidobacterium ( 25 27 , 29 , 31 , 44 , 47 ) (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria we identified are capable of producing some of the volatile compounds previously described in glandular secretions of A. nancymaae (MacDonald et al, 2008; Spence‐Aizenburg et al, 2018a). Many of the chemosignals in these secretions are volatile plant metabolite byproducts, alcohols, and short‐chain fatty acids (MacDonald et al, 2008) that could originate from their natural metabolome or diet (Garber et al, 2019). Given that the subcaudal glands rest directly under the anus, there is likely exposure to fecal flora.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Helicobacter are often reported to have been first isolated from callitrichids suffering from chronic colitis [ 49 , 53 ] and have been shown to cause enteritis in a mouse model [ 53 ]. However, studies of the intestinal microbiota of healthy adult callitrichids, both wild and captive, often yield a high relative abundance of Helicobacter [ 1 , 25 , 42 ]. Furthermore, to date no studies have identified a positive correlation between inflammatory lesions and the presence of Helicobacter [ 18 , 58 ].…”
Section: Discussionmentioning
confidence: 99%